Factors influencing pneumothorax rates of transthoracic CT-guided lung biopsies in a Tertiary centre in Cape Town, South Africa - Richards-Edwards, William H (Division of Radiology, 2021)
Background: Histological sampling of pulmonary lesions is important in diagnosis of lung carcinoma and affects subsequent decisions on specific management. Transthoracic CT-guided lung biopsy is considered an effective option to obtain tissue with low rates of complications, with pneumothorax being the most common. Objectives: To determine the pneumothorax rate of transthoracic CT-guided lung biopsies of focal lung lesions at Groote Schuur Hospital, and assess how procedural, patient and lesion factors influence these results. Methods: A retrospective review of 237 CT-guided lung biopsies performed over a 24-month period. Patient's CT, biopsy reports and post-procedure x-rays were reviewed. The relationship between pneumothorax rates and categorical demographic and clinical variables was analysed with Cochran's trend test. Mann-Whitney U tests were used to assess differences in continuous variables. Factors influencing pneumothorax rates of transthoracic CT-guided lung biopsies in a Tertiary Centre in Cape Town, South Africa. Results: Pneumothorax occurred in 43 (18.1%) of the 237 biopsies. A chest drain was required in 7 of 43 pneumothoraces (16%; 3% overall). Risk factors that were significantly associated with pneumothorax rate include pleural-lesion distance (p<0.001), smaller lesion size (p=0.002), smaller needle gauge (p=0.012) and perilesional emphysema (p=0.011). Patient age, sex, position, lesion location and level of experience of the performing radiologist had no significant influence on the pneumothorax rate. Conclusion: Our post-procedure pneumothorax rate is within the acceptable range when compared to other institutions. Pleural-lesion distance, lesion size, smaller needle gauge and presence of perilesional emphysema were the most significant risk factors influencing pneumothorax rate. Knowledge of these findings may be applicable in pre-procedure planning to reduce complications and useful to local referring clinicians and patients.